Business plan for Lonicera - Babicheva, Anna; Habrmanová, Blanka; Küchler, Jiří; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2020)
The goal of this thesis is to examine the feasibility of a business idea to grow and distribute berries such as honeysuckles and strawberries in Russia. The nature of the topic dictates the use of a variety of analysis to prepare a business plan that enables evaluating the feasibility of starting this agricultural business in Russia. The theoretical part includes the definition of business plan, business model, SWOT, PEST and Porter’s five analysis, the definition and the main aspects of the marketing plan and financial plan. The analytical part contains a developed business plan for the company Lonicera with a variety of analyses performed. This paper can aid entrepreneurs to look deeply into this industry, open or extend their business and anticipate high profits. In other words, this research can be helpful and informative for the future development of that industry in Russia.
Vedoucí práce: Blanka Habrmanová
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2020
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2020
Způsob přístupu: Internet
Keywords: business administration/corporate finance and management [obor bakal. práce]; bakalářské práce; bachelor's theses